Synthesis and biological evaluation of esterified anti-inflammatory drugs with ethylene glycol linkers: cytotoxicity, anti-inflammatory and antioxidant properties - Pascaline M. Deussom; Monique Bassomo Ewonkem; Brice Enang; Michael H. K. Kamdem; Michel A. Mbock; Marthe C. D. Fotsing; Derek T. Ndinteh; Frederic N. Njayou; Flavien A. Toze (Royal Society Open Science)
The development of multifunctional drugs from anti-inflammatory agents is a promising strategy for people with several inflammation-related comorbidities since such medicines could reduce complications, improve health outcomes and lower healthcare costs. In this study, esters of ibuprofen, cinnamic and salicylic acids were synthesized and characterized by spectroscopic methods, with six new compounds identified. Cytotoxicity and anti-inflammatory properties were assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium assay in mouse-derived peritoneal macrophages, which were obtained following an intraperitoneal injection of 0.5 ml of a 2% starch solution. All the tested compounds were safe up to 50% concentrations (2.41 × 10⁻⁴ to 2.41 mM), and monoethylene glycol di-ibuprofen (2) displayed the highest toxicity (IC50 = 4.90 mM). Most compounds were non-toxic below 2.41 mM, and all inhibited nitric oxide (NO) production in a concentration-dependent manner at 0.24 mM. Ibuprofen and cinnamic acid derivatives (2, 3, 5a and 14) exhibited enhanced anti-inflammatory effects, with IC50 = 0.002 mM for monoethylene glycol mono-ibuprofen (3), while fatty-acid ester salicylates (DEW4) demonstrated weaker NO inhibition. Antioxidant tests (2,2-diphenyl-1-picrylhydrazyl, ferric reducing ability of plasma and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS)) showed limited activities, with few compounds reducing the ABTS+ radical (0.1 ˂ SC50 ˂ 0.2 mM). Compounds 3, 5a, 7, 12 and 14 are potential new anti-inflammatory drugs, while 2 may have anti-cancer properties.